A randomized, double blind, dose escalation, first time in human study to assess the safety, tolerability, pharmacokinetics, and antiviral activity of single doses of GSK2485852 in chronically infected hepatitis C subjects. Issue 6 (20th October 2014) - Wilfret, David A.; Walker, Jill; Voitenleitner, Christian; Baptiste‐Brown, Sharon; Lovern, Mark; Kim, Joseph; Adkison, Kimberly; Shotwell, Brad; Mathis, Amanda; Moss, Lee; Lee, Daniel; Yu, Lou; et al.
Abstract This first‐time‐in‐human, randomized, double‐blind, placebo‐controlled, dose‐escalation study assessed the safety, tolerability, pharmacokinetics, and antiviral activity of GSK2485852, a hepatitis C virus (HCV) NS5B inhibitor, in 27 chronically infected HCV genotype‐1 subjects. Subjects received GSK2485852 70, 420, and 70 mg with a moderate fat/caloric meal. Safety, pharmacokinetics, antiviral activity, HCV genotype/phenotype, and interleukin 28B genotype were evaluated. A statistically significant reduction in HCV ribonucleic acid (RNA) was observed after a single dose of 420 mg GSK2485852 (−1.33 log10 IU/mL) compared with placebo (−0.09 log10 IU/mL) at 24 hours post‐dose. Subjects receiving 70 mg GSK2485852 were exposed to concentrations above the protein‐adjusted 90% effective concentration for a short time; none experienced a significant decline in HCV RNA (−0.47 log10 copies/mL). GSK2485852 was readily absorbed; however, the observed geometric mean maximum plasma concentration (Cmax) and area under the curve (AUC) values were significantly lower than expected due to a higher‐than‐predicted‐oral clearance. Co‐administration with food reduced the AUC and Cmax of GSK2485852 by 40% and 70%, respectively. Two metabolites were detected in human blood with one having approximately 50% higher concentrations than those of the parent. GSK2485852 was well‐tolerated and exhibited antiviral activity after a single 420 mg dose in HCV subjects.